Election shutdown (Ethiopia) - Voidly (2021)
CRITICAL severity censorship detected in Ethiopia. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: ET-2021-0002
Keywords: censorship; ET; censorship; critical